THE EFFECT OF EMPOWERMENT, SELF EFFICACY AND JOB SATISFACTION ON JOB PERFORMANCE OF EMPLOYEES IN THE MINISTRY OF FINANCE'S PROCUREMENT ENTITIES - Edy Gunawan; Djaali Djaali; I Ketut R Sudiardhita (IJHCM (International Journal of Human Capital Management), 2017)
The aims and purposes of this research are to identify and assess the direct effect of empowerment, self efficacy, and job satisfaction on job performance.This research is a quantitative research which conducts survey research methods and path analysis. The population in this study are Unit Layanan Pengadaan members in the Ministry of Finance of the Republic of Indonesia which amount to 262 people in which 158 people are used as samples. Analitical tools of path analysis have been conducted to analize the data. Based on the result of examination of the hypothesis, its been concluded that (1) Empowerment has positive and significant effect on Job Performance; (2) Self Efficacy has positive and significant effect on Job Performance); (3) Job Satisfaction has positive and significant effect on Job Performance; (4) Empowerment has positive and significant effect on Job Satisfaction; (5) Self Efficacy has positive and significant effect on Job Satisfaction; (6) Empowerment has positive and significant effect on Self Efficacy.Keywords: Empowerment, Self-Efficacy, Job Satisfaction, Job Performance, Path Analysis